Intracranial pressure and brain monitoring XIV - Schuhmann, Martin Ulrich (Springer Wien, 2012)
Nearly 80 short papers originating from the 14th International Symposium on Intracranial Pressure and Brain Monitoring held in Tuebingen, Germany, in September 2010 present experimental as well as clinical research data related to the naming topics of the conference. The papers have undergone a peer-reviewing and are organized in the following sections: methods of brain monitoring and data analysis, methods of invasive and non-invasive ICP assessment, the role of autoregulation, the role of tissue oxygenation and near-infrared spectroscopy, hydrocephalus/IIH imaging and diagnosis, management and therapy of hydrocephalus, management and therapy of traumatic brain injury, management and therapy of subarachnoid and intracranial hemorrhage, experimental approaches to acute brain disease. The book gives a good overview on the latest research developments in the field of ICP and related brain monitoring and on management and therapy of relevant acute brain diseases.
Keywords: Konferenzschrift